Analysis of the Gut Microbiome of Wild and Captive Père David’s Deer - Sun, Cheng-He; Liu, Hong-Yi; Liu, Bin; Yuan, Bao-Dong; Lu, Chang-Hu (Frontiers in Microbiology, 2019)
Père David’s deer (Elaphurus davidianus or milu) is a highly endangered species originating from China, and many deer are currently being raised in captivity for gradual re-introduction to the wild. Wild and captive deer currently live in the same region but have vastly different diets. In this study, we used 16S rRNA high-throughput sequencing to identify the healthy core microbiome in the gut of wild and captive Père David’s deer and investigate how dietary factors influence the gut microbiome by comparing their differences. A core shared gut microbiome was identified in healthy Père David’s deer, which was similar to that of other ruminants, mainly comprising the phyla Firmicutes and Bacteroidetes. There were no differences in the richness or diversity of the gut microbiome between the wild and captive deer. However, PCA and Anosim demonstrated clear differences in the microbial community structure between the captive and wild deer, which mainly manifested as changes in the relative abundance of 39 bacterial genera. As the majority of these genera were not dominant in the deer gut, no significant difference was detected in functional modules related to the microbiome between the two groups. Therefore, the difference in dietary factors does not appear to affect the healthy core gut microbiome between captive and wild Père David’s deer, suggesting strong co-evolution and the possibility of re-establishment in the wild. These data could guide future applications of population management in Père David’s deer conservation.